The interaction of solar radiation modification with Earth system tipping elements - G. Futerman; M. Adhikari; A. Duffey; Y. Fan; J. Gurevitch; P. Irvine; C. Wieners (Earth System Dynamics)
The avoidance of hitting tipping points has been invoked as a significant benefit of solar radiation modification (SRM) techniques; however, the physical science underpinning this has thus far not been comprehensively assessed. This review assesses the available evidence for the interaction of SRM with a number of Earth system tipping elements in the cryosphere, the oceans, the atmosphere and the biosphere, with a particular focus on the impact of stratospheric aerosol injection. We review the scant available literature directly addressing the interaction of SRM with the tipping elements or closely related proxies to these elements. However, given how limited this evidence is, we also give a first-order indication of the impact of SRM on the tipping elements by assessing the impact of SRM on their drivers. We then briefly assess whether SRM could halt or reverse tipping once feedbacks have been initiated. Finally, we suggest pathways for further research. We find that, when temperature is a key driver of tipping, well-implemented, homogenous, peak-shaving SRM could be at least partially effective at reducing the risk of hitting most tipping points examined relative to the same emission pathway scenarios without SRM. Nonetheless, very large uncertainties remain, particularly when drivers less strongly coupled to temperature are important, and considerably more research is needed before many of these large uncertainties can be resolved.